2021
DOI: 10.3389/fdgth.2021.659088
|View full text |Cite
|
Sign up to set email alerts
|

Examining Response to Negative Life Events Through Fitness Tracker Data

Abstract: Negative life events, such as the death of a loved one, are an unavoidable part of life. These events can be overwhelmingly stressful and may lead to the development of mental health disorders. To mitigate these adverse developments, prior literature has utilized measures of psychological responses to negative life events to better understand their effects on mental health. However, psychological changes represent only one aspect of an individual's potential response. We posit measuring additional dimensions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…Their life stresses mainly stemmed from health adaptation events such as significant changes in their life schedules, poor physical condition, some frustrating events, and other events such as boredom with school, lost love, and arguments or fights with others. These negative life events tend to lead to higher levels of psychological stress and emotional abnormalities among university students, which can adversely affect mental health [ 49 ]. Studies in the United States and Korea have shown that negative emotions like anxiety and depression were associated with the occurrence of gastrointestinal disorders, and an association between emotions and specific defecation habits has been suggested [ 50 , 51 ], which is consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Their life stresses mainly stemmed from health adaptation events such as significant changes in their life schedules, poor physical condition, some frustrating events, and other events such as boredom with school, lost love, and arguments or fights with others. These negative life events tend to lead to higher levels of psychological stress and emotional abnormalities among university students, which can adversely affect mental health [ 49 ]. Studies in the United States and Korea have shown that negative emotions like anxiety and depression were associated with the occurrence of gastrointestinal disorders, and an association between emotions and specific defecation habits has been suggested [ 50 , 51 ], which is consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%